2015
DOI: 10.1021/am509198k
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Mn2O3 Hollow Microspheres as Anode Material of Lithium Ion Battery and Its Conversion Reaction Mechanism Investigated by XANES

Abstract: Hierarchical Mn2O3 hollow microspheres of diameter about 6-10 μm were synthesized by solvent-thermal method. When serving as anode materials of LIBs, the hierarchical Mn2O3 hollow microspheres could deliver a reversible capacity of 580 mAh g(-1) at 500 mA g(-1) after 140 cycles, and a specific capacity of 422 mAh g(-1) at a current density as high as 1600 mA g(-1), demonstrating a good rate capability. Ex situ X-ray absorption near edge structure (XANES) spectrum reveals that, for the first time, the pristine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
75
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(76 citation statements)
references
References 41 publications
1
75
0
Order By: Relevance
“…In this mechanism, the numbers of M–O covalent bonds and M→OH coordination bonds are controlled by the valence and coordination numbers of the metal ion . Here, for the example of M 2+ (e.g., Sn 2+ , Mn 2+ and Pb 2+ ), the coordination number is two …”
Section: Various Precursors To Hierarchically Porous Micro‐/nanostrucmentioning
confidence: 99%
“…In this mechanism, the numbers of M–O covalent bonds and M→OH coordination bonds are controlled by the valence and coordination numbers of the metal ion . Here, for the example of M 2+ (e.g., Sn 2+ , Mn 2+ and Pb 2+ ), the coordination number is two …”
Section: Various Precursors To Hierarchically Porous Micro‐/nanostrucmentioning
confidence: 99%
“…Amongst them, Mn 2 O 3 exhibits distinctive chemical and physical properties [26] . Recently, Mn 2 O 3 nanomaterials have attracted great attention as the electrode materials for Li-ion battery [27][28][29][30] . However, the Mn 2 O 3 nanomaterial as the electrode material for supercapacitor, especially in alkaline electrolyte, is received much less attention.…”
Section: Introductionmentioning
confidence: 99%
“…To date, Mn 2 O 3 materials with different structures have been prepared by different approaches including solvent-thermal method [29] , thermal decomposition [31] , template method [32] and electrospinning [33] . Just as we discussed above, electrospinning technique is a very facile and novel method to prepare 1D nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al. reported Mn 2 O 3 with porous hollow and hierarchical structures, retaining a reversible capacity of 580 mA h g −1 at 500 mA g −1 after 140 cycles . Kong et al.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Sun et al reported Mn 2 O 3 with poroush ollow and hierarchicals tructures, retainingareversible capacity of 580 mA hg À1 at 500 mA g À1 after 140 cycles. [15] Kong et al anchored MnCO 3 nanoparticles on RGO sheets by ah ydrothermal reduction process, and the resultant nanocomposite ex-hibited ah igh specific capacity of up to 857 mA hg À1 after 100 cycles. [16] To date, the electrochemical properties of layered manganese compounds, such as manganese silicate and KMO, are rarely reported as anode materials of LIBs.…”
Section: Introductionmentioning
confidence: 99%